If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 5 = 4(2x + -1) + 9 Reorder the terms: 5 + 9x = 4(2x + -1) + 9 Reorder the terms: 5 + 9x = 4(-1 + 2x) + 9 5 + 9x = (-1 * 4 + 2x * 4) + 9 5 + 9x = (-4 + 8x) + 9 Reorder the terms: 5 + 9x = -4 + 9 + 8x Combine like terms: -4 + 9 = 5 5 + 9x = 5 + 8x Add '-5' to each side of the equation. 5 + -5 + 9x = 5 + -5 + 8x Combine like terms: 5 + -5 = 0 0 + 9x = 5 + -5 + 8x 9x = 5 + -5 + 8x Combine like terms: 5 + -5 = 0 9x = 0 + 8x 9x = 8x Solving 9x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9x + -8x = 8x + -8x Combine like terms: 9x + -8x = 1x 1x = 8x + -8x Combine like terms: 8x + -8x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 4(5x+3)+5=13x+3 | | -13+4x=-52+25 | | 3ax+12ax-36a=0 | | 4+91x=39x+12 | | (x+2)(x+5)=18 | | (3v-6)/3v | | .5(x+30)+1.1x=79 | | -(-2a-3)-5=-3(a-6) | | c^2d^2-4cd+4=0 | | -4(x+1)=-1(x+5) | | a^6-7a+a-7=0 | | 3(25-b)+b=35 | | x^3-7x^2+6=0 | | -2-(-8)-7+3= | | 9x^2-20x+2=0 | | -4k-(3-7k)=15 | | 4b-6b+7=9 | | 7=5c+22-10c | | 2w-7w+3=-22 | | 46=4x-4+6x | | -7w-(w+4)=12 | | 5(x-2)+3=-3(2x+1)-6 | | 7m+20-10=-25 | | 36r^2-60r+25=0 | | 15y-(-5y+36)=24 | | 12+x+9=37 | | x^2-6x-y^2+7=0 | | -98y^2-26=0 | | x+15+19=41 | | 40x+35y=720 | | 9aq^4-9an^4=0 | | 4y-(2y+2)=18 |